PENERAPAN MODEL COOPERATIVE LEARNING TIPE TGT TERHADAP HASIL SHOOTING SEPAK BOLA SMPN 2 SIANTAN - Ardian Ardian; Mimi Haetami; Andika Triansyah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
Abstract                        Students pay attention to the explanation from the teacher about the shooting tec hnique of the game of soccer using the inside and outside legs. Alternative TGT types in soccer learning problems. The method used was the experimental method, the study design used pre-experimental design, and the study design used the design of one group pretest-posttest design. The population of the study was all eighth grade students of SMPN 2 Siantan 2018/2019 school year as many as 120 students. The study was 30 students. Data collection technique used were soccer shooting tests. Data were analyzed by descriptive analysis and using t-test (influence test). From the results of the research conducted, it can be concluded that there is an effect of the application of cooperative models of learning TGT type on the learning outcomes of soccer shooting in class VIII students of SMPN 2 Siantan. The results of the t-test analysis indicate that the tcount (9,241) and ttable (2,045) or (9,241> 2,045). The magnitude of the percentage of influence given by learning by applying the cooperative models of learning TGT type on the learning outcomes of soccer shooting in class VIII students of SMPN 2 Siantan is 26,79%.Keywords: Cooperative Learning Model, Teams Game Tournament, Learning Results for Shooting Football.